2019
DOI: 10.12688/f1000research.17587.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the induction of labor

Abstract: The rate of labor induction is steadily increasing and, in industrialized countries, approximately one out of four pregnant women has their labor induced. Induction of labor should be considered when the benefits of prompt vaginal delivery outweigh the maternal and/or fetal risks of waiting for the spontaneous onset of labor. However, this procedure is not free of risks, which include an increase in operative vaginal or caesarean delivery and excessive uterine activity with risk of fetal heart rate abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 111 publications
1
42
0
5
Order By: Relevance
“…Induction of labour is indicated when risk due to continuation of pregnancy outweighs that of termination of pregnancy [1] . Induction with use of prostaglandins is widely accepted as a standard method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of labour is indicated when risk due to continuation of pregnancy outweighs that of termination of pregnancy [1] . Induction with use of prostaglandins is widely accepted as a standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Labour must be induced artificially when benefits of termination of pregnancy outweighs those of continuing pregnancy. Currently a quarter of all pregnant women in industrialized countries undergo artificial induction of labour [1] . For induction of labour two different approaches are used, which are often used in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of labor (IOL) is a common practice in obstetrics and is followed in many countries with rates ranging from 1.4–35% [ 1 , 2 ]. A recent publication revealed that the rate of IOL was 23.4% in the United States, 22.1% in the United Kingdom, 4.4% in African regions, 11.4% in Latin America, and 12.1% in Asian countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The case of uterine rupture was recorded in the study that used 100 µg of misoprostol [17]. The rate of induction is on the increase, 35.5% in Sri Lanka, 24.5% in USA, 33% in Europe, 12.7% in Ibadan Nigeria and 11.5% in Abakaliki [3] [18]. Studies on maternal mortality in Ebonyi State have reported high maternal mortality ratios both in the rural and urban areas where uterine rupture was reported as a major cause due to injudicious use of uterotonics [19] 2) To determine the effective and safe dosage of misoprostol for cervical ripening and induction of labor for our clients.…”
Section: Introductionmentioning
confidence: 99%